Exploring the Relationship between Consumer Protection and Product Liability : Civil and Islamic Perspectives - Muhammad Hafiz, Mohd Shukri; Rahmah, Ismail; Ruzian, Markom (Malaysian Consumer and Family Economics Association (MACFEA), UPM, 2024)
Consumer protection is an aspect which aims to ensure that consumers are always given adequate protection from a legal perspective and also to increase the level of consumers' trust in the quality of goods and services, which will, in turn, contribute to the economic growth of a nation. However, today, issues surrounding product liability cases are no longer uncommon, where consumers or third parties face the risk of suffering injury or property damage due to the existence of defects in a particular product. Thus, the main objective of this study is to analyze the relationship between consumer protection and product liability from both civil and Islamic perspectives. The type of research being carried out is doctrinal legal research. The data sources, including case law and statutory provision, are analyzed using content and critical analysis methods. The results show that according to civil and Islamic perspectives, consumer protection in the context of product liability plays a crucial role in conferring legal protection to consumers who are adversely affected by the use of particular products that pose a risk to health and safety. Further, the authors expect that the results of this study shall contribute new and significant knowledge by proving that the aspect of consumer protection is not only related to product liability issues from a civil perspective, but it is also can be evaluated from the Islamic perspective, which the earlier researchers have rarely discussed.